(untitled) (International Journal of Physiology, 2020)
Background and Aim: Smoking directly or indirectly has serious impact on health of an individual. During smoking various chemicals and toxic substances are released into the air such as nicotine, carbon monoxide which can be inhaled by the people nearby indirectly. Pregnant mothers may passively inhale carbonmonoxidewhen exposed to such environment. Maternal Carbon monoxide passes through placenta and enters foetalblood combine with foetalhaemoglobin forming foetal carboxy haemoglobin. Foetal carboxy haemoglobin in turn makes oxygen unavailableto foetal tissues which could be the reason for various poor outcomes in unborn foetus such as low birth weight, intra uterine growth retardation with higher rates of perinatal mortality. This study is aimed at measuring the expired air carbon monoxide levels in passively smoking pregnant women that can be correlated with exposure to passive smoking. Method and Materials: 100 antenatal women of gestational age between 26 to 34 weeks with and without exposure to passive smoking were measured for carbon monoxide levels in their expired air usingsimple, portable non invasive carbon monoxidemonitor. Statistical Analysis: Data analysis was done with unpaired student t test. P value of <0.05 was taken to be significant. Results: No significant statistical difference is observed between cases and control groupsin expired aircarbon monoxide levels. Discussion and Conclusion: The lesser half life of carbon monoxide in exhaled air. The longtime interval between the exposure and the time of testing, the metabolic changes associated with pregnancy could have made this test inconclusive. Though gold standard blood analytic method cannot be replaced by this breath monitors,it can be used as a simple portable noninvasive toolto educate pregnant women to avoid exposure to passive smoking.